The Importance of Communication Process in Negotiation - Rizka Adinda; Cecep Safa'atul Barkah; Nurillah Jamil Achmawati Novel (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2022)
Negotiations that involve two or more parties in reaching an agreement cannot go off from the communication in its process. Therefore, excellent and practical communication skills will make negotiations effective as well. This study aims to analyze the importance of the communication process in negotiation through the qualitative descriptive method, or more accurately, a secondary data analysis method using existing data, and then express into words that describe the essential role of the communication process in negotiation. The study results showed that negotiation, as one business activity involving two or more parties in its process, cannot be separated from communication to reach a mutual agreement. Therefore, communication is exchanging messages from one party to another. Therefore, communication plays a vital role in negotiations. A negotiator with good communication skills must be able to convey a message that the other party quickly understands and also be able to read or understand the intent of the message sent by another party, both verbally and non-verbally. Thus, both parties can compromise so that an agreement meets each party's needs as expected. Based on the results obtained, the communication process in negotiations is one of the critical success factors that aim to reach an agreement beneficial for each party involved.